SoSpider: A bio-inspired multimodal untethered soft hexapod robot for planetary lava tube exploration - Mokarram Hossain (Science China Technological Sciences, 2023)
Soft robots have tremendous potential for applications in various fields, owing to their safety and flexibility embedded at the material level. Soft robots, especially bio-inspired soft legged robots, have become one of the most active fields of current research in robotics thanks to their superior mobility and ability to face complex terrains. However, it is arduous to establish a dynamic simulation model for soft robots, owing to their hyper-redundant degrees of freedom, hyper-elasticity, and nonlinearity of their soft structures. In this study, we designed, simulated, and fabricated a hexapod robot that achieves walking, crawling, pronking, and rolling with wheeled legs plus a soft body capable of shape change. A robot prototype was fabricated using 3D printing technology and soft silicone pneumatic networks. Actuators, battery power, and control boards were integrated into the body of the robot for untethered locomotion. We have explored the capabilities of the robot in different conditions, especially in scenarios that simulate lunar and Martian environments, demonstrating the motion performance of the robot. The results have shown promising potentials of the developed robot for future applications in planetary lava tube exploration. Our experimental and simulation results also show good agreements that indicate the potential predictive roles of simulation tools for soft robot design, planning, and control.